Factors Affecting Information Quality of Local Government Financial Statement - Fakhri Triasa Anggriawan; Ivan Yudianto (Universitas Padjadjaran, 2018)
This study aims to determine the factors that affect the information quality of West Bandung District local government financial information. Government financial statement should meet qualitative characteristics. This research uses qualitative method and data completion with interview technique and reports to 17 informants, which are heads of sub finance section in Regional Work Units of West Bandung District. Data analysis is done by data reduction, then presents data and conclude data obtained according to the data analysis method for qualitative research. The results of this study indicate the factors that affect the information quality of West Bandung District Financial Statements are the application of Government Accounting Standards, human resources quality, internal control system, utilization of information technology, organizational commitment, the role of internal auditors, assets, external factors, and the operational fund management of special schools for West Bandung District Education Office.